PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS POE (Predict, Observe, Explain) UNTUK MENINGKATAKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI PESERTA DIDIK KELAS V - Ventri Adetia Jumintri; Endang Widi Winarni; Irwan Koto (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
This study aims to improve the higher-order thinking skills of fifth grade students through the development of POE-based worksheets to improve higher-order thinking skills. This research was a development research using the ADDIE model which consists of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were students of MI Ikhwanul Djauhariah, Bengkulu City. Class 5A MI Ikhwanul Djauhariah Bengkulu City totaled 21 students as the control class, and class amounted to 21 students as the Experiment class. The object in this research is POE-based LKPD. Data collection were carried out by interviews, documentation, questionnaires, and paper-pencil tests. The data analysis technique used Aiken's V and interrater reliability, t-test and N-gain. The results showed that the validation of content, language and graphics as well as student responses to LKPD were in good category. The results of the t-test showed that the value of sig.(2-tailed) < 0.05 so that there was a difference in the average learning outcomes of students using POE-based worksheets in the experimental class and the control class. Based on the N-gain test, which is 56.09% in the effective to improve higher order thinking skills in science learning.